Mercúrio total em rações, filés e fígado de tilápia do Nilo de pisciculturas - Botaro, D.; Longo, R. T.; Galvão, P. M. A.; Lino, A. S.; Torres, J. P. M.; Meire, R. O.; Pizzochero, A. C.; Malm, O. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2011)
Fish consumption is considered the most important source of contaminant exposure for humans beings, and farmed fish can be exposed to contaminants via feed supply. Total mercury concentrations (THg) were determined in the muscle, liver and feed of farmed Nile tilapia (juveniles and adults) from four different fish farms (net cage and pond systems), by a flow injection mercury system. Mercury concentrations observed in muscle and liver were lower than the values recommended by Brazilian regulatory agency (Anvisa) for fish of 500 μgTHg.kg-1 and fish farm NC1 showed the highest THg concentrations when compared to the other fish farms. There are reports of strong gold exploration around 1987 in this region, where more than 100 ferries worked in mining this metal. The low THg concentrations found in muscle of farmed tilapia in this study confirm the low tendency of these fish to accumulate Hg, since they are less exposed to this contaminant than wild tilapias. Other factors, such as higher growth rate and shorter life span when compared to wild fish can contribute to marked reductions in THg concentrations. Body lipid content can also influence contaminant concentrations accumulated in an organism. Lipid concentrations in the present study in fish muscle ranged from 0.7 to 4.3%, noting that lipid levels were higher in NC than in PS fish farms. Thus, higher THg concentrations in the muscle tissue with lower lipid concentrations (PS farms) were observed. The low THg concentrations found in the analysed fish feed (5.2 – 33.2 μg.kg-1) can be also responsible for the low concentration in fish muscle. Therefore, continuous monitoring of contaminant concentrations in fish feed is necessary due to variations in the use of ingredients, which cause variations in the concentrations of undesirable substances in commercial feeds. In relation to tissue analysis, a statistically significant difference (P < 0.05) between Hg accumulation in liver and muscle was observed, where the liver presented the highest concentrations. Regarding fish age difference, a statistically significant difference (P < 0.05) was observed when comparing Hg accumulation between adults and juveniles, with larger fish having higher THg concentrations than smaller fish. Differences in bioaccumulation rates can be related to the different nutritional needs of fish in different life stages. Thus, fish age is an important factor, due to changes in food supplies, as well as the increased exposure time of the animals to Hg.